The robustness of carbon fibre members bonded to aluminium connectors in aerial delivery systems. Issue 1 (31st December 2016) - Aldoumani, Nada; Haddad Khodaparast, Hamed; Cameron, Ian; Friswell, Michael; Jones, David; Chandrashaker, Arun; Sienz, Johann
Abstract: In this paper a framework for robust design solution of an adhesively bonded joint between a composite material and an aluminum connector is developed. To this end, an approach has been developed to automate the process of robust design by linking Ansys workbench and an in-house MATLAB code. The model employed in this study investigated the possibility of joining composite materials to aluminum components which is a problematic process in terms of preparation, implementation, etc. Before designing such a join, it is necessary to fully understand the behaviour of the proposed aluminum connector with the carbon fibre member. To achieve this, the investigation of the adhesive layer's behaviour and the uncertainties involved in such structures was identified. The behaviour of the adhesive between the carbon fibre composite and the aluminum connector was modelled based on the assumption that this layer acts as a "spring system" within a "cohesive" zone. Initially, the properties of Permabond ET5428 BLACK adhesive were used for validating the finite element model using the obtained test data. A robust design method is then employed to identify the right adhesive for the joint which not only maximizes the debonding force and sliding distance but is also robust with respect to the variation in its mechanical properties. A wide range of adhesive properties have been employed and a robust design technique based on uncertainty analysis is proposed.